2010
DOI: 10.1007/s10620-010-1277-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Severity, and Etiology of Drug-Induced Acute Pancreatitis

Abstract: The diagnosis of drug-induced acute pancreatitis seems to be underestimated because of the difficulties in determining the causative agent and the need for a retrospective re-evaluation of the suspected causative factors. The disease is more probable in younger persons, women, and patients suffering from Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
82
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 20 publications
0
82
1
5
Order By: Relevance
“…Drug-induced pancreatitises are a rare cause of pancreatitis which represents about 3-5% of all causes (3,4), but it is difficult to establish its real incidence because of the lack of prospective studies and the underdiagnosis of this entity. They are more frequent in young patients, women and Crohn's disease (3), the latter being probably related with the drugs taken for the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug-induced pancreatitises are a rare cause of pancreatitis which represents about 3-5% of all causes (3,4), but it is difficult to establish its real incidence because of the lack of prospective studies and the underdiagnosis of this entity. They are more frequent in young patients, women and Crohn's disease (3), the latter being probably related with the drugs taken for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…They are more frequent in young patients, women and Crohn's disease (3), the latter being probably related with the drugs taken for the disease. It represents a diagnostic challenge since quite often the drug is not related to the episode of pancreatitis, which is finally catalogued as an idiopathic pancreatitis (3,4). This difficulty derives from the fact that they are not usually considered in the initial differential diagnosis, and establishing its relationship with the origin of the pancreatitis is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A national survey performed in Japan in 1999 reported that 1.2% of all cases of AP were drug induced. Drug-induced AP is rare but should not be overlooked in a patient who presents with idiopathic AP [6]- [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report of 170 cases of pancreatitis cared for at a single academic medical center in the Czech Republic concluded that drugs were the most likely cause in 5.3 % of cases, making drugs the third most frequent cause of AP aft er gallstones and alcohol ( 3 ). Another report, involving a retrospective review of 138 patients diagnosed with AP from a single center in France, attributed the etiology to drugs in 6.5 % of cases.…”
mentioning
confidence: 99%